Evaluation of ectopic pregnancy after assisted reproductive technology in infertility center of Shariati Hospital - A Alyasin; M Agha Hossinei; A Khademi; H Saeidi Saeidabady (JRI, 2001)
Ectopic pregnancy (EP) is a serious complication of pregnancy. Incidence of EP after normal pregnancy is %1 overall, but after assisted reproductive technology (ART) increases to %5. Many factors including: previous EP, tubal surgery, tubal pathology, previous infection of female genital tract, infertility and ART are identified as risk factors for EP. In this study 47 EP were studied over 4 years in infertility treatment center of Shariati Hospital which control group was chosen from uncomplicated pregnancies after ART. Two groups were matched in age, duration of infertility, mode of treatment. Incidence of secondary infertility and tubal factor were significantly higher in EP group. Incidence of previous EP, pelvic surgery, tubal pathology, manipulation of uterus and fibroma was significantly higher in EP group. Uterine embryo transfer was introduced as a risk factor for EP. Meticulous evaluation of risk factors need prospective studies.
Keywords: Ectopic pregnancy, Assisted Reproductive Techniques, Risk factor, Tubal Factor, Infertility